2016
DOI: 10.1177/0042098015616895
|View full text |Cite
|
Sign up to set email alerts
|

Urban encounters limited: The importance of built-in boundaries in contacts between people with intellectual or psychiatric disabilities and their neighbours

Abstract: People with intellectual disabilities or psychiatric disorders who live in ordinary neighbourhoods often have little contact with fellow residents without disabilities. Recent research suggests that we should not strive for warm contacts based on familiarity and shared values between utterly different groups in urban areas. Daily life between people with and without disabilities is described as a process in which boundaries are negotiated. This study builds on that observation. It was based in a middle sized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 51 publications
3
49
1
2
Order By: Relevance
“…First, being born and raised in the neighbourhood, and consequently having a lot family and acquaintances (personal relationships) nearby, contributes to the OVERMARS-MARX Et Al. public familiarity that appears to be important for a feeling at home in the neighbourhood (see also Blokland & Nast, 2014;Bredewold et al, 2016;Wiesel & Bigby, 2014). This finding is in line with the studies of Wiesel, Bigby, and Carling-Jenkins (2013) and Bredewold et al (2016), who found local shops to be of great importance to the people with intellectual disabilities, because they provide recognition and thus contribute to public familiarity (Blokland & Nast, 2014). Our participants narrated stories about the valuable contacts they have with shop assistants in local shops.…”
Section: Reflecting On the Ecological Model And Practical Implicationssupporting
confidence: 86%
See 1 more Smart Citation
“…First, being born and raised in the neighbourhood, and consequently having a lot family and acquaintances (personal relationships) nearby, contributes to the OVERMARS-MARX Et Al. public familiarity that appears to be important for a feeling at home in the neighbourhood (see also Blokland & Nast, 2014;Bredewold et al, 2016;Wiesel & Bigby, 2014). This finding is in line with the studies of Wiesel, Bigby, and Carling-Jenkins (2013) and Bredewold et al (2016), who found local shops to be of great importance to the people with intellectual disabilities, because they provide recognition and thus contribute to public familiarity (Blokland & Nast, 2014). Our participants narrated stories about the valuable contacts they have with shop assistants in local shops.…”
Section: Reflecting On the Ecological Model And Practical Implicationssupporting
confidence: 86%
“…These findings suggest that public familiarity could be identified as a significant aspect of neighbourhood social inclusion from the perspective of people with intellectual disabilities (e.g., Blokland & Nast, 2014;Bredewold, Tonkens, & Trappenburg, 2016;Van Alphen et al, 2009). In cases where public familiarity was absent, participants felt less connected to their neighbourhood.…”
Section: Discussionmentioning
confidence: 90%
“…Maximal warm encounters between local residents and psychiatric survivors are not necessary, and as Bredewold et al . () show, may not even be desirable. A modest modicum of recognition may suffice to address discursive erasure.…”
Section: Symbolic Reinscription: Territorial Destigmatization Withoutmentioning
confidence: 99%
“…More recently, researchers have begun to disrupt the binary between community presence and participation using ideas about encounter and the diverse and fluid social networks that characterize modern cities (Bigby & Wiesel, 2011Bredewold, Tonkens, & Trappenburg, 2016;Laurier & Philo, 2006;Wiesel, Bigby, & Carling Jenkins, 2013). Convivial encounters are a particular type of encounter-social interactions that are neither free mingling in public places (presence) nor based on long-term relationships (participation as understood by O'Brien & Lyle, 1987) but where there is a shared identity or activity and a sense of pleasantness or warmth (Fincher & Iveson, 2008).…”
mentioning
confidence: 99%
“…Gestures such as a nod or a wave "contribute to a sense of recognition and of 'feeling at home' in a neighbourhood" (Bredewold et al, 2016;p. 3381).…”
mentioning
confidence: 99%